Phytosociological study of coastal flora of Devbhoomi Dwarka district and its islands in the Gulf of Kachchh, Gujarat - Das, L.; Salvi, H.; Kamboj, R. D. (International Journal of Scientific Research in Biological Sciences, 2019)
The study described the diversity and phytosociological attributes of plant species (trees, shrubs and herbs) in coastal areas of Devbhoomi Dwarka District and its islands in the Gulf of Kachchh. A random sampling method was employed in this study. A total of 243 plant species were recorded of which trees and shrubs represented with 30 specieseach. Grasses & sedges were also represented by 30 species and 29 species were climbers. Among the tree and shrub species, Prosopis juliflora showed the highest density (373.51 ind. /ha), frequency (63.50.67%), relative density (30.19.7%), relative frequency (24.41%) and relative abundance (7.68%).Regarding herb species, Aristida redacta represented the highest density (3.97ind./sq.m) and frequency (39.02%). Moreover, the highest importance value index was measured in Prosopis juliflora (62.28) among trees & shrubs and Aristida redacta (31.51) among herbs. The Abundance/Frequency ratio of trees, shrubs and herb species showed contagious distribution pattern within the study area. The present study also includes α diversity (Shannon diversity index, Simpson`s Index, species richness, evenness index) of the coastal terrestrial plants.